Conqueror and hero : the search for Alexander - Krensky, Stephen; Farquharson, Alexander (Boston : Little, Brown, 1981)
Outlines the life of Alexander, a charismatic individual who was simultaneously the king of Macedonia, pharaoh of Egypt, and emperor of Persia.
Keywords: Alexander, -- the Great, -- 356 B.C.-323 B.C. -- Juvenile literature; Alexander, -- the Great, -- 356 B.C.-323 B.C.; Kings, queens, rulers, etc; Greece -- Kings and rulers -- Biography -- Juvenile literature